Relationship between CA-125 Levels and Extrauterine Spread in Endometrial Cancer Endometrioid Type at Dr. Soetomo General Hospital Surabaya - Brahmana Askandar; Andika Adi Saputra (National Cancer Center - Dharmais Cancer Hospital, 2021)
Background: Endometrial cancer is the sixth most common malignancy incidence in women worldwide. The surgical staging in endometrial cancer management such as bilateral salpingooophorectomy and lymphadenectomy is not a routine procedure for all endometrial cancer patients. Therefore, a biomarker to estimate the presence of endometrial cancer metastases to adnexa and lymph nodes is needed. This study aims to find out the level of cancer antigen 125 (CA-125) in endometrial cancer endometrioid type and the relationship between the level of CA-125 and the incidence of adnexal metastases, lymph node metastases, clinical stage, and myometrial invasion.Methods: This observational analytic study used a direct observational design. The in-vitro quantitative examination was performed to measure CA-125 levels using CA-125 Advia Centaur CA-125 Kit. Fischer exact test used to analyzed CA-125 levels with the subject characteristics. All the statistical analyses were performed using SPSS v. 21.0.Results: Of the 30 research subjects with the characteristics of the most age groups of 51–60 years (60%), with the most multiparous parity (73.3%), grade III (43.3%), myometrial invasion > 50% by 66.7%, early-stage (63.3%), the incidence of adnexal metastases (30%), and the incidence of lymph node (LN) metastases (10%), a significant relationship between CA-125 levels and lymph node (LN) metastases was found with a p = 0.041 and the phi association of 0.016 and between CA-125 levels and adnexal metastases with a p = 0.035 and the phi association of 0.026. There was also a significant relationship between CA-125 levels and the clinical stage (advanced stage) with p = 0.004 and the phi association of 0.002. There is no significant relationship with a p = 0.702 and a phi association value of -0.098.Conclusions: CA-125 can be used as a tumor marker to predict the presence of extrauterine metastases (adnexa & lymph nodes).